A Bibliometric Analysis of Web-Based E-Modules in Science Education: Trends and Visualization - Adawiah, Rabiatun; Muslihatun, Fitri (Indonesian Publication Center, 2026)
This study conducts a bibliometric analysis of scientific publications regarding web-based e-modules in science education over the 2017–2026 period. Data were retrieved from the Dimensions.ai database (830 publications) and Google Scholar (859 publications), subsequently analyzed using VOSviewer software to identify publication trends, country contributions, collaboration patterns, and keyword clusters. The results indicate a significant increase in the number of publications, particularly since 2020 due to the acceleration of online learning during the COVID-19 pandemic, reaching a peak in 2025. Indonesia dominates in terms of publication volume (210 documents), followed by the United States and China, although the latter two countries exhibit higher citation impacts and collaboration strengths. Keyword analysis reveals a primary focus on the integration of web technology with innovative pedagogical approaches such as STEM, Problem-Based Learning (PBL), Project-Based Learning (PjBL), augmented reality, Google Sites, flipbooks, and the development of 21st-century skills (critical thinking, self-regulation, digital literacy, and ethnoscience). The trends have evolved from simple material digitalization toward interactive, adaptive, and student-centered learning ecosystems, including the integration of AI, gamification, and local wisdom. This research identifies gaps such as the lack of equitable international collaboration, a shortage of long-term evaluations, and the limited integration of advanced technologies. Consequently, it is recommended that future bibliometric approaches be integrated with empirical and longitudinal studies. Furthermore, to enhance citation impact and research quality, Indonesian researchers must strengthen international collaborations through cross-country research, joint publications in high-impact journals, and active engagement in global research networks to match the academic influence held by the United States and China. Overall, web-based e-modules have become a key innovation in the transformation of science education toward learning that is more effective, inclusive, and relevant to the demands of the digital era.